Antiretroviral Therapy Adherence During and Postbreastfeeding Cessation Measured by Tenofovir Levels in Hair. (1st November 2022) - Nematadzira, Teacler G.; Murnane, Pamela M.; Odiase, Osamuedeme J.; Bacchetti, Peter; Okochi, Hideaki; Tallerico, Regina; Chanaiwa, Vongai M.; Vhembo, Tichaona; Mutambanengwe-Jacob, Mercy T.; Louie, Alexander; Chipato, Tsungai; Gandhi, Monica; et al.
Abstract : Background: We examined change in antiretroviral treatment (ART) adherence after breastfeeding (BF) cessation using hair tenofovir (TFV) concentrations as an objective metric of medication consumption. Methods: A subset of postpartum women in Zimbabwe randomized in IMPAACT PROMISE to take ART while BF and post-BF cessation had hair TFV measured longitudinally. Using linear mixed-effect models, we estimated differences in hair TFV levels after BF cessation, accounting for trends in levels over time regardless of BF status and change in slope after breastfeeding cessation. We also estimated the relative risk of viremia (>50 copies/mL) per doubling of hair TFV concentration. Results: Among 55 women (median age 26, interquartile range 24–29 years), hair TFV levels (n = 305) were available for a median of 9 visits per woman between 3 and 29 months postpartum. Hair TFV levels ranged from undetected to 0.25 ng/mg (median 0.04 ng/mg). Controlling for trends since delivery [decline of 2.2% per month, 95% confidence interval (CI): −5.3 to 1.0], TFV levels averaged 24.4% higher (95% CI: −5.1 to 63.1) post-BF cessation than during BF, with no change in slope (0.0% per month, 95% CI: −3.8 to 3.9). Postpartum, 42% of women were ever viremic. Higher TFV levels were strongly protective; relative risk of viremia per doubling of TFV was 0.52 (95% CI: 0.43 to 0.63; P < 0.0001). Conclusions: Leveraging an objective metric of ART use, we observed modestly declining adherence across the postpartum period, but no additional decline associated with breastfeeding cessation. High viremia frequency and varying postpartum TFV levels observed highlight the importance of enhanced adherence support with viral load monitoring among postpartum women.